Bale farmer field day assesses results of Africa RISING farmer-based crop trials in Ethiopia - International Livestock Research Institute (International Livestock Research Institute, 2015)
The Africa RISING project in Ethiopia has been organizing several field days since 2013 for a range of participants at its 4 sites and 8 research kebeles. Field days have proved to be a strong mechanism for cross-project learning as they have engaged farmers, extension, NGOs, Universities, market dealers, industries and other value chain actors across the whole project stakeholder spectrum. This video reports from a field day held in Sinana woreda in December 2014. Video from January 2015.